Implementation of Supervision & Enforcement of Sanctions Against Notaries Who Do Not Carry Out Their Position - Farah Syifa Setyaningrum; Sri Endah Wahyuningsih; Widhi Handoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Notary as a position of trust means nothing if it turns out that those who carry out their duties as Notary Public are untrustworthy, so that between the position of the Notary and the official (who is carrying out the duties of the position of Notary) must be in line like the two sides of a coin that cannot be separated. Supervision and guidance is needed so that the Notary in carrying out his duties and responsibilities as given by the relevant basic regulations, is always carried out on a predetermined path, not only the legal route, but also on the basis of moral and professional ethics, with the aim of ensuring legal protection and certainty. law for the public who use Notary services, in this case the authorized party, is the Notary Supervisory Council (MPN). The purpose of this research is to analyze the implementation of supervision and enforcement of sanctions against notaries who do not carry out their positions properly in the city of Tegal. To analyze the obstacles and solutions to the implementation of supervision and enforcement of sanctions against notaries who do not carry out their positions properly in the city of Tegal. The method used in this research is the empirical juridical method, which is a legal research method that seeks to see the law in a real sense or can be said to see, examine how the law works in society. The results of this study ultimately provide an answer that the Notary Supervisory Council must be able to improve the quality and quality of notary services. Notaries who have committed violations must accept the consequences, namely getting sanctions because there are still many Notary candidates who are still waiting for the formation of positions in each region. If they are not competent in carrying out their duties, the Notary Supervisory Council, in this case the MPP, will impose sanctions on disrespectful dismissal, in accordance with Article 7 of the Law on Notary Position Number 2 of 2014 concerning Amendments to Act No. 30 of 2004 Notary Position. The guidance carried out must be based on a high awareness and understanding of moral and ethical values.[1] Habib Adjie, Sanksi Perdata dan Administratif Terhadap Notaris Sebagai Pejabat Publik, Bandung : PT. Refika Aditama. p. 35.